MOTIF DAN KEPUASAN REMAJA KOTA DENPASAR MENONTON TAYANGAN HOTMAN PARIS SHOW MELALUI YOUTUBE - Subudi Darma, Made Dwi; Dewi Pascarani, Ni Nyoman; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT Hotman Paris Show is a talk show program that is aired on iNews TV and also had a large audience on YouTube. This study aimed to find out what theRmotive and how the satisfactionRof teenager in the city ofFDenpasar in watching Hotman Paris Show. This research used the theory ofEUses and Gratifications and usedDdescriptive quantitative method. SamplingFtechnique in this research wasSpurposive sampling. Data wereFobtained by distributing questionnairesFusing Likert scale. TheAanalytical technique usedd is descriptive statistics by looking at the mmean score of motives and ssatisfaction. The results showedDthat there are one motives that can be ssatisfied in watching tthe Hotman Paris Show that is the motif of information. Motives that can not be satisfied in watching the Hotman Paris Show is the motive of personal identity ,integrity and social interaction and the motiveFof entertainment. Keywords: Denpasar, Hotman Paris Show, Motive, Satisfaction